Prophetic Educational Theory on Marital Intimacy: Thematic Digital Hadith Analysis - Danusiri, Danusiri; Imron, Ali; Budiman, Mamdukh; Esfahani, Ali Banaeian; Amkhatirah, Emad (Institut Muslim Cendekia, 2025)
Pregnancy represents a critical phase in Muslim family life, requiring ethical and educational guidance rooted in authentic sources. This study aimed to explore Prophetic educational theory concerning marital intimacy during pregnancy as derived from the sayings of Prophet Muhammad (ﷺ). Employing a qualitative library-based research design, the study utilised the HadithSoft application to retrieve ḥadīth from 14 canonical collections. The keyword “pregnancy” guided thematic extraction, and only maqbūl (accepted) narrations were included. Data analysis applied Miles and Huberman’s eleventh strategy—constructing logical chains of evidence—to synthesise normative principles. The findings revealed eight core themes forming a Prophetic framework for marital ethics during pregnancy. These results contributed to Islamic reproductive ethics and offered practical implications for antenatal education, healthcare counselling, and family policy, thereby bridging classical guidance with contemporary bioethical challenges.